The mediating role of mindful entrepreneurial marketing (MEM) between production and consumption. Issue 1 (8th July 2014) - Uslay, Can; Erdogan, Emine
Abstract : Purpose: – The purpose of this paper is to introduce and explore the tenets of the mindful entrepreneurial marketing (MEM) construct and to illustrate its mediation effect between production and consumption. Design/methodology/approach: – Based on the existing mindfulness and entrepreneurial marketing research, this paper explores tenets of MEM and presents a basic taxonomy to identify mindful production and consumption practices, and opportunities for MEM initiatives. Findings: – The study proposes that the combination of mindfulness and entrepreneurial marketing approach provides an ideal match where both consumers and mindful producers can become more mindful and prosper. As a new construct, MEM has the potential to alleviate lack of consumption, to create awareness about overconsumption and, ultimately, to enhance societal welfare by increasing the efficiency of markets by enabling more effective usage of society's resources. Originality/value: – This paper is the first study that focuses on the MEM construct. In this respect, the study contributes to mindfulness, mindful marketing, entrepreneurial marketing and the general marketing literature.